PENGARUH VARIASI AIR GAP TERHADAP DOSIS SERAP PENYINARAN BERKAS ELEKTRON PADA PESAWAT LINAC SIEMENS / PRIMUS M CLASS 5633 - Galih Puspa Saraswati; Eko Hidayanto; Evi Setiawati (Youngster Physics Journal, 2014)
The effect of the variation of the air gap absorbed dose in electron beam irradiation has conducted. In the particular case of electron beam irradiation often can not use the SSD 100 cm due to the influence of the use of the applicator so that the patient's body should be granted an extension of the SSD or air gap at the irradiation. In this study the calculation of the effective SSD, absorbed dose, the air gap correction factor and verification of absorbed dose was performed using the inverse square law and the correction of the output electrons. The method utilized an inverse square law load value of each electron beam irradiation to determine the effective SSD, while the determination of absorbed dose and the air gap correction factor correction using electron output. The results of the calculation states that the effective SSD of 82,2 cm – 109 cm wide field size and is proportional to the electron energy. Absorbed dose and the air gap correction factor proportional to the field size and inversely proportional to the variation of the air gap while the value of the absorbed dose itself is varied between 64,80 cGy to 108,0 cGy as well as the value of the correction factor of the air gap is between 0,869 – 1,000. Correction dose verification of absorbed dose value is still below the value specified tolerances AAPM TG40 is equal to 99,10% - 103,0%. Variations of growing air gap causes the smaller absorbed dose.Keywords: air gap, effective SSD, air gap correction factor, dose normalization